Christensenella intestinihominis MNO-863 improve obesity and related metabolic disorders via SCFAs-induced GLP-1 hormone secretion - Kong, Ping; Xian, Yibo; Lao, Canshan; Huang, Baojia; Zhang, Dongya; Tai, Lihong; Zhao, Yingying; Pu, Zilun; Lan, Zhou; Zhang, Chenchen; Liu, Zhenzhen; Xiao, Chen; et al. (Frontiers in Nutrition, 2025)
The intestinal microbiota has been demonstrating a strong correlation with the etiology and progression of obesity and metabolic disorders, thus presenting a novel approach to addressing this issue. In this study, we screened and revealed the anti-obesity efficacy of the viable Christensenella intestinihominis (C. intestinihominis) MNO-863 in diet-induced obese mouse models. MNO-863 reduced body weight by 10% from baseline and over 15% compared to high-fat control in the dose-dependent manner. It also ameliorated obesity-related metabolic indices including hyperlipidemia, hyperglycemia, glucose and insulin resistance, and non-alcoholic steatohepatitis (NASH). The anti-obesity efficacy of MNO-863 monotherapy is comparable to that of Liraglutide (GLP-1 analogue), and the combination of MNO-863 and Liraglutide has potential synergistic anti-obesity therapeutic effect. Treatment with MNO-863 significantly raised the levels of intestinal hormones, such as glucagon-like peptide-1 (GLP-1) and peptide YY (PYY), and concurrently increased the abundance of short-chain fatty acids (SCFAs) producing bacteria, resulting in higher colonic concentrations of propionate. These changes are correlative with previous observations suggesting that propionate–G-protein coupled receptor 43 (GPR43) interaction may contribute to GLP-1 and PYY release; causality remains to be established. A 28-day oral toxicity study in Sprague Dawley (SD) rats showed that MNO-863 Fermental Powder at doses up to 1.2 × 1012 colony-forming unit (CFU)/animal/day caused no observed adverse effects. As a second-generation probiotic, MNO-863 is expected to provide a new, safer drug option for patients with obesity and related complications.